$Γ$-Transformation of Parabolic Kählerian Spaces Related by an Almost Geodesic Mapping π2 $π_2 (e = 0)$ - Grigoreva, T. I. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For parabolic Kählerian spaces, we obtain a new form of the main equations and construct a Γ-transformation that enables one to convert a certain pair of related parabolic Kählerian spaces into an infinite sequence of different related parabolic Kählerian spaces.